PERNAFASAN BUTEYKO BERMANFAAT DALAM PENGONTROLAN ASMA - Juwita, Lisavina; Sary, Ine Permata (Universitas Fort De Kock Bukittinggi, 2019)
The epidemiological problems of mortality and morbidity of asthma still tend to be high, predicts that the current number of asthma patients in the world reaches 334 million people, continues to increase by 400 million people by 2025 and there are 250 thousand deaths from asthma including children (WHO). The purpose of this study to determine the difference between controlling the asthma before and after the implementation of Buteyko breathing. This research uses Quasy Exsperiment design design with pretest - posttest. The population of this research are all patients suffering from asthma disease in Working Area of Bukittinggi City Health Care Cente 2018 which amounted to 44 people and the number of samples in the research is 15 people. Statistical test results obtained p value 0,000 means there is a difference between controlling the asthma before and after the implementation of respiratory Buteyko. Recommendation for the Health Care Center Leader to conduct socialization and training so that all nurses have the same ability in implementing breathing techniques Buteyko on asthma sufferers